2003
DOI: 10.1002/app.12082
|View full text |Cite
|
Sign up to set email alerts
|

Vulcanization kinetics of natural rubber–organoclay nanocomposites

Abstract: ABSTRACT:The effect of the incorporation of a bentonite on the vulcanization kinetics of natural rubber was investigated by means of both cure-meter testing and differential scanning calorimetry (DSC) under dynamic and isothermal conditions. The vulcanization curves showed that the modified clay behaved as an effective vulcanizing agent, accelerating the vulcanization reaction of the elastomer. A marked decrease in the induction time and optimum cure time of the elastomer were observed in the presence of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
1
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(141 citation statements)
references
References 27 publications
(40 reference statements)
8
119
1
2
Order By: Relevance
“…Some methods to analyze the rubber vulcanization have been performed, such as, Bideau et al [3] have used the short wave infra red irradiation, Jaunich et al [4] monitored the reaction of vulcanization using ultrasonic online, Salgueiro et al [5] used SANS, or Pazur et al [6] used NMR. DSC was used to analyze the vulcanization reaction as conducted by Chough et al [7], Manchado et al [8], and Ding et al [9]. Rheometer is one of the methods to analyze the vulcanization reaction and has been still very popular in rubber technology.…”
Section: Introductionmentioning
confidence: 99%
“…Some methods to analyze the rubber vulcanization have been performed, such as, Bideau et al [3] have used the short wave infra red irradiation, Jaunich et al [4] monitored the reaction of vulcanization using ultrasonic online, Salgueiro et al [5] used SANS, or Pazur et al [6] used NMR. DSC was used to analyze the vulcanization reaction as conducted by Chough et al [7], Manchado et al [8], and Ding et al [9]. Rheometer is one of the methods to analyze the vulcanization reaction and has been still very popular in rubber technology.…”
Section: Introductionmentioning
confidence: 99%
“…Many data were reported in the literature, supporting these conclusions, in rubbers such as NR (hexadecyltrimethyl ammonium, octadecyltrimethyl ammonium, tetraoctyl phosphonium, triphenyl vinylbenzyl phosphonium, octadecylamine chloridrate were used as intercalants) [81][82][83][84][85][86], SBR (Mt/octadecyltrimethylamonium) [87], (NBR (octylamine; dodecylamine and octadecylamine chloridrates were the intercalants) [76]. A reduction of the activation energy for sulphur based NR crosslinking was found by using a bentonite modified with octadecylamine chloridrate [83,88].…”
Section: Vulcanization Of Rcnmentioning
confidence: 69%
“…A reduction of the activation energy for sulphur based NR crosslinking was found by using a bentonite modified with octadecylamine chloridrate [83,88]. OC could thus present a warning, as they could lead to premature scorching but, at the same time, they could present the chance of performing vulcanization reactions at lower temperatures.…”
Section: Vulcanization Of Rcnmentioning
confidence: 99%
“…Most previous studies about the vulcanization kinetic of RCNs indicted that addition of OMC would considerably increase curing rate and crosslinking density of various rubber compounds, including NR [24,25], ENR [26], BR [27,28], SBR [29], EAR [30], NBR [31], and NBR/SBR blend [32]. On the other hand, some studies [12,33] on EPDM/OMC systems shown that addition of OMC prolonged the optimum curing time and reduced the cross-linking density of the composites.…”
Section: Effects Of Omc On the Curing Processmentioning
confidence: 99%